Application of ZIF-67 as a crosslinker to prepare sulfonated polysulfone mixed-matrix membranes for enhanced water permeability and separation properties - Jiulong Yin; Hai Tang; Di Liu; Tingting Huang; Lei Zhu (Water Science and Technology, 2021)
High-performance sulfonated polysulfone (SPSf) mixed-matrix membranes (MMMs) were fabricated via a nonsolvent-induced phase separation (NIPS) method using zeolitic imidazolate frameworks-67 (ZIF-67) as a crosslinker. Acid-base crosslinking occurred between the sulfonic acid groups of SPSf and the tertiary amine groups of the embedded ZIF-67, which improved the dispersion of ZIF-67 and simultaneously improved the membrane strzcture and permselectivity. The dispersion of ZIF-67 in the MMMs and the acid-base crosslinking reaction were verified by energy-dispersive X-ray spectroscopy (EDX), X-ray diffractometry (XRD), Fourier-transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS). The pore structure analysis of MMMs indicated that filling ZIF-67 into SPSf enhanced the average surface pore sizes, surface porosities and more micropore in cross-sections. The crossflow filtrations showed the MMMs have higher pure water fluxes (57 to 111 L m−2 h−1) than the SPSf membrane (55 L m−2 h−1) but also higher bovine serum albumin (BSA) rejection rate of 93.9–95.8%, a model protein foulant. The MMMs showed a higher water contact angle than the SPSf membrane due to the addition of hydrophobic ZIF-67 and acid-base crosslinking, and also maintained high thermal stability evidenced by the thermogravimetric analysis (TGA) results. At the optimal ZIF-67 concentration of 0.3 wt%, the water flux of the SPSf-Z67-0.3 membrane was 82 L m−2 h−1 with a high BSA rejection rate of 95.3% at 0.1 MPa and better antifouling performance (FRR = 70%). Highlights An SPSf-matrix ultrafiltration (UF) membrane was developed by blending with hydrophobic ZIF-67.; ZIF-67 has good dispersibility and compatibility with SPSf of weak acid-base interaction.; Simultaneous enhancement in the permeability and selectivity of the MMMs.;